Current scenario and future prospects of plant growth-promoting rhizobacteria: an economic valuable resource for the agriculture revival under stressful conditions. (30th July 2020) - Khoshru, Bahman; Mitra, Debasis; Khoshmanzar, Elaheh; Myo, Ei Mon; Uniyal, Navendra; Mahakur, Bhaswatimayee; Mohapatra, Pradeep Kumar Das; Panneerselvam, Periyasamy; Boutaj, Hanane; Alizadeh, Mehrdad; Cely, Martha Viviana Torres; Senapati, Ansuman; et al.
Abstract: The biotic and abiotic stresses are key constraints for food quality, crop yield and global food security. It is necessary to take action to cope with global threats caused by abiotic and biotic stresses such as a reduction in precipitation, increasing drought, salinity, improper temperature, heavy metals, nutrient deficiency and invasion of plants pathogenic microbes, which lead to the reduction of agricultural crops productivity. Plants are severely affected by these stresses and have impaired functioning. One of the strategies to cope with abiotic and biotic stresses is taking advantage of the potential of soil microbes, including plant growth-promoting rhizobacteria (PGPR). The solution is completely environmentally compatible and has no negative effects on the environment. Effective PGPR have a substantial role in biotic and abiotic stresses management, reduce chemical fertilizers and increase the yield of plant cultivars by affecting elemental cycling and nutrient management. These beneficial bacteria can stimulate plant growth under abiotic and biotic stress conditions via mechanisms such as the production of phytohormones, ACC (1-aminocyclopropane-1-carboxylate) deaminase, exopolysaccharides, siderophore, organic acids, nitrogen fixation, phosphate solubilization, various osmolytes, systemic resistance induction, etc. In this review, the role of the PGPR as a new strategy was investigated that may be responsible for the increase in crop productivity and eventually by effectively answering biotic and abiotic stresses leads to food security.